A new subass. of Dinaric altimontane beech forest Ranunculo platanifolii-Fagetum Marinček et al. 1993 var. geogr. Calamintha grandiflora Marinček 1996 seslerietosum autumnalis from Mt. Snežnik - Marinček, Lojze (Annales. Series historia naturalis, 1997)
A new, the most thermophilous subassociation Ranunculo platanifolii-Fagetum Marinček et al. 1993 var. geogr. Calamintha grandiflora Marinček 1996 seslerietosum autumnalis subass. nova is described. Its differential species are: Sesleria autumnalis, Carex alba, Cirsium eristihales and Sorbus aria.
Keywords: bukovi gozdovi; flora; gozdovi; Snežnik; vegetacija